Factors Influencing Halal Cosmetics Actual Purchase Behaviour Among Muslim Women In Indonesia: Religiosity As A Moderator - Nurafni, Rubiyanti (2021)
Nowadays, Indonesia not only undergoes rapid development in the halal industry, but also experiences changes in consumer behaviour. Along with the advancement of Indonesia’s halal industry, the Indonesian government has set a vision to make Indonesia the largest halal economy and global halal hub by giving full support to the development of halal certification. Even though full support is provided by the government for developing halal industry in Indonesia, there are still some issues pertaining to halal purchasing behaviour in Indonesia, especially in the cosmetic industry. For that reason, the aim of this study was to examine the relationship between factors that influence actual purchase behaviour towards halal cosmetics among Indonesian consumers. This study was expected to broaden the understanding of relationships among variables of Theory of Planned Behaviour (TPB) which served as a basic theoretical model. In this study, the framework of TPB was extended by proposing new additional variables which were brand personality and religiosity as moderators between casual pathways of the existing constructs. This study provided information for both halal cosmetics industry and the government regarding the prediction of consumer actual purchase behaviour towards halal cosmetics. The confirmatory factor analysis was employed to obtain halal cosmetics brand personality. The partial least squares technique was employed to evaluate the statistical significance of the proposed pathways.